1997
DOI: 10.1583/1074-6218(1997)004<0152:eaacoe>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Endoleak as a Complication of Endoluminal Grafting of Abdominal Aortic Aneurysms: Classification, Incidence, Diagnosis,and Management

Abstract: The inability to obtain or maintain a secure seal between a vessel wall and a transluminally implanted intra-aneurysmal graft is a complication unique to the evolving technique of endovascular aneurysm exclusion. Because the term "leak" has long been associated with aneurysm rupture, the term "endoleak" is proposed as a more definitive description of this phenomenon. Embracing both persistent blood flow into the aneurysmal sac from within or around the graft (graft related) and from patent collateral arteries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
272
0
14

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 702 publications
(287 citation statements)
references
References 18 publications
1
272
0
14
Order By: Relevance
“…Endovascular abdominal aortic aneurysm repair with metal endoprosthesis (EVAR) has become particularly significant as an alternative to traditional surgery, due to less early mortality and complications and a low rate of aneurysm rupture [1,2,[12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular abdominal aortic aneurysm repair with metal endoprosthesis (EVAR) has become particularly significant as an alternative to traditional surgery, due to less early mortality and complications and a low rate of aneurysm rupture [1,2,[12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the classification most recommended by the vascular surgeon's societies is the one developed by White et al, that was modified in recent years, dividing endoleaks into five types (19)(20)(21) . This classification is based on the origin of the blood flow into the aneurysmal sac and has direct implication on the treatment required for each case.…”
Section: Discussionmentioning
confidence: 99%
“…Multidetector CT angiography is the imaging method of choice for the followup of these patients, because of the high sensitivity of the method in the identification of endoleaks and other complications associated with the procedure (19,25) .…”
Section: Discussionmentioning
confidence: 99%
“…24 Other studies reported finding signs of previous endoleaks in post-EVAR aneurysm ruptures; therefore, endoleaks are aggressively evaluated and treated if they persist beyond the 6-month follow-up, unless the aneurysm sac has shrunk. 14,25,26 Because persistent T2Es are significant contributors to late adverse outcomes such as aneurysm rupture, conversion to open repair, aneurysm sac growth and the need for reintervention, several treatment options are available for the management of T2Es (Box 3). However, the management of T2Es is hotly debated because of diverse personal experience and beliefs concerning the long-term outcome of the various approaches.…”
Section: Discussion Natural History Risk Factors and Surveillance Ofmentioning
confidence: 99%